The Development of a Creative Program for Digitizing the Potential of Tourism Villages through Sport Tourism in Singkarak Lake, Solok Regency - Nugroho Susanto; Hanif Badri; Windo Wiria Dinata; Tiok Wijanarko (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Increasing the number of tourist visits to a destination is an indicator of the success of an effective marketing promotion strategy. The selection of an effective marketing promotion strategy that is in accordance with market trends is an absolute must. One of the effective media in the promotion of destination marketing is to use digital marketing media and sport tourism. Lake Singkarak is one of the villages that makes tourism as one of the sectors driving the economy of its people. Lake Singkarak has considerable potential including cultural tourism, nature tourism and educational tourism. Lake Singkarak has a weakness in terms of marketing promotion, so that the increase in the number of visits is not significant.Community service programs are expected to be the solution. Activities carried out are village tourism workshops, and interesting sport tourism to be able to travel on Lake Singkarak.